Epineural sleeve neurorrhaphy: Surgical technique and functional results - A preliminary report - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
This study was conducted to evaluate the effect of epineural sleeve neurorrhaphy on peripheral nerve regeneration. A total of 12 Lewis rats were divided in two groups of 6 rats each. In group 1, the rat sciatic nerve was transected and repaired using the conventional epineural technique with four sutures. In group 2, the epineural sleeve technique was introduced with two sutures only. Functional recovery was evaluated at 1, 2, 4, 8, and 12 weeks by walking track analysis (sciatic function index [SFI]), mean limb circumference ratio, and severity of toe contracture. Although the SFI at 12 weeks revealed no difference between the two groups (-88.39 +/- 10.75 conventional group, -77.35 +/- 17.06 epineural sleeve group), significant differences in SFIs were detected at 4 and 8 weeks, with better functional recovery in group 2 rats (4 weeks: 125.92 +/- 22.73 conventional group, -99.17 +/- 5.45 epineural sleeve group; 8 weeks: -96.65 +/- 4.73 conventional group, -72.82 +/- 17.11 epineural group; p < 0.05 for both time points). Mean limb circumference ratio was not significant at all time points. At 12 weeks, all animals in the conventional nerve repair group developed severe toe contractures whereas only 2 animals in epineural sleeve repair group had contracture (p < 0.05). In this study, the epineural sleeve technique demonstrated a faster functional recovery when compared with the conventional technique, as confirmed by SFI and toe contracture grading.
Keywords: REGENERATION; INVIVO